FENOMENA SAMPAH DAN PARIWISATA BALI - Ni Ketut Sutrisnawati; A.A.A Ribeka M.Purwahita (Institut Pariwisata dan Bisnis Internasional, 2018)
Garbage is an inseparable part of human life. Garbage is produced by humans as waste in fulfilling their needs. However, the presence of the garbage cause major environmental problems and threat to the tourism sector in Bali. Tourist comes to Bali to enjoy the splendour of its nature and cultures, but they have to see the reality that the island is less than their expectations. In contrast to Bali's image as a sun-drenched tropical island and the last paradise on earth, the ugly truth is that the island is awash in garbage. The beaches littered with plastic bags, bottles, straw, plastic wrappers. This phenomenon is getting worst especially on rainy season where most of garbage which is washed into waterways by the daily rains and carried into the sea resulting big mount of waste in the coast area. Â Complaints came from tourists about this issue is an indication that they feel uncomfortable with the presence of this garbage. If there is no serious action and commitment to solve this issue, slowly but surely there are more tourist will skipping to visit Bali. Regarding to this issue, Balinese have no one to blame but themselves. Garbage becomes a big problem because people have a thought that illegal dumping is the norm. The active participation of all stakeholders such as goverment, industry, local community also visitor is needed to overcome this problem to realize sustainability of environment and tourism of Bali. Â Keywords: Garbage, Tourism, Sustainable TourismÂ